Factors behind the dynamics of land use evolution: case of Lebanon - Walid Al-Shaar; Olivier Bonin (SN Applied Sciences, 2021)
Abstracts Monitoring and understanding the evolution of land use and land cover is a key factor for many environmental studies as well as for policymakers. Moreover, policymakers are interested in understanding the factors that have a significant impact on land use change. This paper analyses the dynamics of land use change in Lebanon between the years 1984 and 2019 and identifies the main factors behind this process. The use of LandSat satellite images enables the creation of land use maps at several periods and the monitoring of the evolution of built up areas as well as of green areas. Five periods emerge from this analysis, for which it is possible to propose explanatory factors, after an in-depth qualitative analysis. Within the framework of Structural Equation Models, a Confirmatory Factor Analysis is carried out to determine the impacts of several factors related to governance and financial data. Moreover, the urban sprawl is further investigated and explained by cultural, environmental, and infrastructural factors. The main results reveal that the development of built up areas is highly dependent on good funding conditions, whereas banking conditions and weak governance are correlated. The case of Lebanon presents specificities probably linked to historical and cultural considerations that deserve to be studied in future works. In the form of recommendations, new land use policies should be enacted to ensure sustainability in the form of an equilibrium between the urban development, from one side, and the preservation of natural resources and good environmental conditions on the other side. This could comprise the preservation of natural zones; the subsidization of the cultivation profession; and the encouragement of urban densification instead of horizontal sprawl.